Social participation: how does it vary with illness, caring and ethnic group? - Platt, Lucinda (Colchester, 2006)
"It has long been accepted that lack of social participation in wider society is one aspect or one definition of poverty. Current concerns with the extent and distribution of social capital as both a measure of a good society and as means to upward mobility also emphasise the importance of social contacts and networks to the well-being of individuals and communities. While research has often focused on ‘civic participation’ and the measurement of trust, more informal social bonds are also a crucial part of individuals’ social capital. Moreover, informal social capital or social participation might be particularly important for those whose circumstances make them already more vulnerable to marginalisation, exclusion or poverty. For example, social interaction has been argued to be conducive to better outcomes for those with health problems; and there is an extensive literature which aims to chart and explain the role of ‘ethnic capital’ in the life chances of minority ethnic groups. I use the British Home Office Citizenship Survey 2001 for England and Wales to explore the impact on four aspects of lack of social engagement of long-term illness, caring for someone with such an illness, and ethnicity. Controlling for a range of characteristics and examining the relationships separately for men and women there is evidence that between them, the four measures reveal an underlying propensity for reduced social contact. Other things being equal, illness has little association with reduced social participation, but caring does seem to affect opportunities for sociability. Members of some ethnic groups are less likely to engage in neighbourly social visiting than others, and these differences are little affected by income level. By contrast differences in ‘going out’ across groups can largely be explained by differences in income. Overall, social engagement among male Bangladeshis and to a lesser extent Pakistanis is high, whereas Black Africans and Black Caribbeans, especially women, are notable for their lack of opportunities for social engagement compared with their otherwise similar peers. They would appear to be particularly at risk of social isolation, with consequences for their current and future welfare."